The Influence of MSME Readiness in Adopting a Digital Accounting System on the Effectiveness of Business Financial Management in Maron District, Probolinggo Regency - Nindyah Siska Handayani; Ahdiyat Agus Susila; Cici Widya Prasetiyandari (Majapahit Journal of Islamic Finance and Management, 2026)
This study aims to analyze the readiness of Micro, Small, and Medium Enterprises (MSMEs) to adopt digital accounting systems and examine its effect on the effectiveness of business financial management. This research employed a quantitative approach with a causal associative design. The population consisted of 1,070 MSMEs in Maron District, Probolinggo Regency, with a sample of 101 respondents determined using the Slovin formula. Data were collected through Likert-scale questionnaires and analyzed using simple linear regression with IBM SPSS Statistics 26. The results indicate that MSME readiness to adopt digital accounting systems has a positive and significant effect on the effectiveness of financial management, as evidenced by a significance value of 0.000 (<0.05) and a regression coefficient of 0.687. Furthermore, the coefficient of determination (R Square) was 0.777, indicating that 77.7% of the variation in financial management effectiveness is explained by digital accounting system adoption readiness. The study concludes that enhancing MSME digital readiness can improve the effectiveness of financial management and support transparent and accountable financial practices in accordance with Islamic financial principles.